Review on the Recent Development of Fatty Hydrazide as Corrosion Inhibitor in Acidic Medium: Experimental and Theoretical Approaches - Hassan, A. (MDPI, 2022)
In recent years, numerous research work has been conducted in order to find the most practical and cost-effective solution for corrosion issues in the oil and gas industry. Several studies have revealed that fatty hydrazide derivatives are the most suitable corrosion inhibitor for the application in the said industry. These compounds can also act as effective corrosion inhibitors in acidic medium with inhibition efficiency greater than 95. This review summarizes and discusses the recent corrosion inhibitor development in acidic media from 2017 until 2021, focusing on fatty hydrazide derivatives. The significant findings and mechanisms of inhibition have been elucidated. In addition, intake on the computer simulation studies of fatty hydrazide inhibition properties is also included in this review. Finally, some suggestions for future research on corrosion inhibitors have been recommended. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.